THE PERCEPTION OF GOLDEN PROPORTION OF TEETH BY LAYPERSON PRESENTING AT OUTPATIENT DEPARTMENT OF TERTIARY CARE HOSPITAL OF PESHAWAR - Gulalai Jan; Shahab Adil; Ghazala; Shama Gul; Zarwis Akbar; Nimra Mahmud (Pakistan Oral & Dental Journal, 2024)
Objective: The objective of this research is to investigate how laypersons perceive the golden proportion in dental aesthetics.Materials and Methods: A cross-sectional study was conducted at Peshawar Dental College after the Institutional Review Board (IRB) approval. Simple sample randomization was used to choose pairs of young adults (n = 40) who had completed orthodontic therapy but not yet received orthodontic treatment based on age and gender. ImageJ software was used to measure the maxillary anterior teeth's golden proportion. The Oral Aesthetic Subjective Impact Scale (OASIS) was a layperson-designed questionnaire that assessed dental aesthetic concerns. Using Student's t-test, the data were compared. We used the Mann-Whitney test to assess the OASIS scores. Logistic regression was used to examine relationships. Î±= 5% was used for all statistical calculations.Results: The mesiodistal widths of the maxillary central incisors and canines were not assessed to have a golden ratio in either group (p0.05).Conclusion: In individuals receiving orthodontic treatment, whose self-perception of oral beauty is higher, the central incisor perceived width is closer to the golden proportion.
Keywords: Orthodontics; Golden proportion; Layperson perception